Communal Conflicts in West Kalimantan: The Urgency of Multicultural Education - Kurniawan, Syamsul; Miftah, Muhammad (Dinamika Ilmu: Jurnal Pendidikan, 2021)
Communal conflicts between ethnic groups in West Kalimantan still leave a post-conflict residue which is problematic to this day. For example, in Sambas, although at present it can be said that the relationship between ethnic Sambas Melayu and Madurese outside Sambas seems to be subsiding, the research findings showed that it is not the real fact in Sambas. Even in the community, there is still a stigma about Sambas as an unsafe area for the Madurese ethnicity. This social fact shows that the efforts of a dialogue forum to reconcile the two ethnicities only succeeded in resolving conflicts on the surface, but it failed to resolve the core of the conflict, namely stereotyping. Although it is not as complicated as in Sambas, inter-ethnic stereotypes are also a problem for two other post-conflict areas, namely Sanggau Ledo and Pontianak. Because education is considered to have a strategic role in building multicultural awareness and correcting stereotypes, in this context, multicultural education is considered relevant to be developed in schools in West Kalimantan. It is the focus of this study. This study is the result of qualitative research, whose data is obtained by the authors from observations, interviews, and documentation. The informants in this study were people in post-conflict areas in West Kalimantan, namely in Sanggau Ledo, Sambas, and Pontianak with ethnic backgrounds of Malay, Dayak, and Madura. In this study, the authors used an interactive data analysis method which included data reduction, data presentation, and conclusion/verification proposed by Miles, Huberman, and SaldaÃ±a.